Deep Vein Thrombosis and Pulmonary Embolism in the Setting of Mycoplasma Infection - Sandal Saleem; Brian Berman (Case Reports in Medicine)
Thirteen-year-old female twins presented one week apart with documented Mycoplasma pneumoniae respiratory infection. Each developed venous thrombosis and pulmonary emboli in association with transient self-limited para-infectious anti-phospholipid antibodies. Comprehensive evaluation revealed no identifiable genetic prothrombotic variables. Both children recovered after receiving antibiotics and anticoagulation therapy. Thrombotic complications associated with Mycoplasma pneumoniae infections are rare, particularly in children; the occurrence of this complication in identical twins has not been previously reported.